Do elevated TSH levels predict early pregnancy loss in ART patients?. (1st December 2016) - Gingold, Julian A.; Zafman, Kelly; Rodriguez-Purata, Jorge; Whitehouse, Michael C.; Lee, Joseph A.; Sandler, Benjamin; Copperman, Alan B.
Abstract: Introduction : The upper limit of normal TSH has been revised from 5 mIU/L to 2.5 mIU/L. We sought to evaluate IVF patients and the association between abnormal TSH and early pregnancy loss. Methods : A retrospective study of patients who had TSH levels measured within the 2 weeks prior to their fresh autologous IVF cycles (2002–2014). Cohorts were stratified by oocyte age (<35, [35–38), [38–41), [41–43) and ≥43 years), and TSH level [(0–0.5], (0.5–2.5], (2.5–5], and (5–23) mIU/L]. Patients were followed until pregnancy loss or delivery. Model was assessed by chi-square of ANOVA with significance at p < 0.05. Results : TSH was abnormally elevated (>5 mIU/L), mildly elevated ((2.5–5] mIU/L) or suppressed (≤0.5 mIU/L) in 46, 317 and 65 of the 1201 total cycles, respectively. Treatment resulted in 630 pregnancies, 524 clinical pregnancies and 409 deliveries. Pregnancy loss rates were increased in patients ≥38 yo ( p < 0.001) but not [35–38) yo ( p = 0.40) compared with those <35 yo. Early pregnancy loss rate was not associated with TSH level ( p > 0.30) compared with euthyroid patients after adjusting for oocyte age. Conclusion : Early pregnancy loss rate in IVF patients appears to have no relation to recent TSH levels.